Wound infection caused by Neisseria zoodegmatis, a zoonotic pathogen: a case report. Issue 3 (10th March 2021) - Merlino, John; Gray, Timothy; Beresford, Rohan; Baskar, Sai Rupa; Gottlieb, Thomas; Birdsall, Jacob
Abstract : The isolation of Neisseria zoodegmatis from a 63-year-old female presenting to the emergency department following a cat bite injury to her right hand is described in this report. N. zoodegmatis, also known as Centers for Disease Control (CDC) group EF-4b, is considered to be a zoonotic pathogen, and is usually associated with dog or cat bites. Despite the potential of this organism to cause serious soft tissue infections, it can be overlooked in routine clinical laboratories due to its slow growth characteristics and when the history of animal bite is not provided to the laboratory. This case highlights the importance of appropriate clinical history provision to the microbiology laboratory to help provide important information about potential pathogens and allow microbiologists to optimize culture and identification methods. The introduction of tools such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) into clinical laboratories allows identification and the interpretation of results to be performed within a few minutes of isolation on proper culture media, as opposed to traditional methods, whose slowness may be problematic, as shown in this case report.